ASN dalam Pendidikan Tinggi: Transformasi dan Akreditasi - Anwar Sanusi; Masduki Asbari; Ardi Ardiansah (Journal of Information Systems and Management (JISMA), 2023)
The purpose of establishing the competence of the Department is not with a prescription determined by national standards but with a quality framework determined by national standards of higher education, to realize the standards developed by universities referring to their pramwork, internal quality assurance becomes not detailed in this regulation and therefore we provide flexibility of academic autonomy to universities by utilizing Creation and Innovation which is widely opened in accordance with Candy-53, Year 2023. External quality assurance system For 3 years It has transformed the Accreditation System based on the Independent Accreditation institution in accordance with the provisions of the Constitution 12-2012 Using an Independent System Developed By (LAM). In this study report using a descriptive qualitative method by taking notes because the source of the data obtained by listening to the oral narration from the Yotube channel of Dtjen Dktiristek entitled "Socialization of Permendikbudristek Number 53 of 2023". Higher education has the fastest potential in building superior human resources Therefore, the new higher education standards serve as a framework only for the quality of higher education delivery to no longer be descriptive and perspective such as formulation or regulating in detail The simplification carried out does not eliminate the value of the previous regulation but only changes and gives authority to high desert to be able to organize and adjust the internal quality between them makes the final project given No longer has to be in the form of a thesis can be in the form of Projeck, Prototype, Research or other forms in accordance with the competence of graduates so that students can innovate more in the community environment . The BAN PT and LAM Accreditation Instruments are in accordance with Permendikbudristek Number 53 of 2023, which will be carried out in joint coordination between the Belmawa Directorate, BAN PT, LAM PT, and the Institutional Directive. For the assessment of International Accreditation recognized by the Government, an assessment will be carried out by the Assessment Team consisting of BAN PT, LAM and the Team appointed in accordance with the Ministry of Education and Culture and Technology 306/2022. then the Higher Education of Research and Technology reviewed and harmonized the Regulations of the Ministry of Education and Culture and Technology which Kemendikbudristek affected.